Pengaruh Kepemimpinan Transformasional, Integritas Perilaku Dan Budaya Organisasi Terhadap Kinerja Karyawan - Kurniati, Nenny; Rojuaniah, Rojuaniah (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Employee performance has a dominant influence in the process of achieving company goals. Various efforts to improve employee performance are expected to enable employees to provide optimal capabilities for the benefit of the company. This study aims to analyze the effect of transformational leadership, behavioral integrity and organizational culture on employee performance, data collection was carried out by distributing questionnaires to 60 employees. The analytical method used in this study is multiple linear regression using the statistic software. The results showed that transformational leadership had no effect on employee performance, behavioral integrity had no effect on employee performance and the organizational culture had a effect on employee performance at a laundry service company.